Investigation of dynamic pressure fluctuations in closed hydraulic circuits as a function of centrifugal pump speed gradients. Issue 1 (June 2021) - Büker, J; Laß, A; Witte, M; Wurm, F-H
Abstract: Electrical consumers, such as pumps, contribute towards the stable operation of the electrical power grid due to active and reactive power consumption. If the consumers are indirectly connected to the grid via power electronic converters, the positive contribution is reduced or non-existent. Consequently, the ability to compensate imbalances within the power grid is greatly reduced. A research project founded by the European Union is focusing on investigations to utilize power converter technology of pump drives for grid stabilization. But in order to stabilize the fluctuating power grid frequency rapid adjustments of the pump speed are required, which can cause major troubles in the hydraulic system. For instance, rapid changes in pump speed are causing the emission of hydro acoustic pressure waves into the pipe system, which are exciting the structure of the hydraulic system and lead to undesirable vibrations and noise emissions. Most critical is the direct excitation of natural frequencies in the entire piping system based on the inherent pressure fluctuations caused by transient fluid flow and pump speed changes. Converter control for grid-adaptive speed adjustment is only possible as long as there is no significant increase in dynamic pressure fluctuations in the whole hydraulic system. For this purpose, a research pump is operated with different rotational speed gradients in a closed hydraulic circuit. Dynamic pressure sensors were used to record the resulting pressure fluctuations at various locations of the hydraulic system. Additionally, an outlook towards an active reduction of the dynamic pressure fluctuations by means of a specially developed hydrodynamic actuator is given. These results are an initial step but of particular interest towards the knowledge of permissible grid adaptive speed control regimes, which can be applied to a pump in a hydraulic piping system.